Working With Text in Teaching Concise Presentation - Gabdesheva Astra (Research Reviews, 2026)
The ultimate goal of speech development is to develop the ability to perceive others’ thoughts and express them verbally and in writing, using language correctly and appropriately in accordance with the purpose and conditions of communication. This task is solved in all Russian language and literature lessons, but special speech development lessons play a special role in this. The amount of hours allocated for such lessons is determined by the Russian language program. Programs at the A1-A2 levels of elementary grades assume the largest number of hours for speech development lessons. At this stage of learning, students are practically assimilating: the text; the theme and main idea of the text; the outline of the text (simple and complex); types of texts (narrative, description, reasoning); style of speech (colloquial, artistic, scientific, official business, journalistic); detailed, concise, selective reproduction of the text. Based on the assimilation of these concepts, work is organized on the formation of appropriate skills in various types of speech activity: listening, speaking, reading and writing.